Przekształcenia koncepcji środków zabezpieczających w polskim prawie karnym - Góralski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The article provides a combined analysis of Polish criminal law regulations, both past and present, with regard to restraining measures, whether involving confinement or not, therapeutic or non-therapeutic. In this context, the author distinguishes the following periods: 1918–1939, 1944–1950, 1951–1968, 1969–1990 and the current legal situation in the area, trying to indicate how views, doctrines and directions of normative transformations applying to measures of restraint in the above periods affected the scope of legal regulations contained in the Criminal Code of 1997. He also describes diverse scholarly concepts of restraining measures from the past classical, relating to protective guarantee, positivist and eclectic. In addition, he examines the current criminal law regulations regarding restraining measures. The analysis is concluded with the author’s proposals of possible amendments to the existing regulations on measures of restraint.
Keywords: środek przymusu; kara dodatkowa; środek postkarny; środek ochronny; ośrodek adaptacji społecznej; zakład dla przestępców niepoprawnych; nadzór opiekuńczy